2022
DOI: 10.2337/db21-0908
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor YY1 Is Essential for Normal DNA Repair and Cell Cycle in Human and Mouse β-Cells

Abstract: Identifying the mechanisms behind the β-cell adaptation-to-failure is important to develop strategies to manage type 2 diabetes (T2D). Using db/db mice at early stages of the disease process, we took advantage of unbiased RNAseq to identify genes/pathways regulated by insulin resistance in β-cells. We demonstrate herein that islets from 4-week-old non-obese and non-diabetic leptin-receptor deficient db/db mice exhibited downregulation of several genes involved in cell-cycle regulation and DNA repair. We identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Approximately, 90% of patients have varying degrees of motor retardation and intellectual disability (Cherik et al, 2022). Animal experiments on mice showed that knockout of the YY1 gene at the early stage of cortical development increased the apoptosis rate of neuroepithelial cells (NECs) and neural precursor cells (NPCs) and led the cell to stay in the G1/S phase (Martins Peçanha et al, 2022), which led to neurodevelopmental defects by affecting the development of neurons. This is consistent with the case of motor retardation as the first manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 90% of patients have varying degrees of motor retardation and intellectual disability (Cherik et al, 2022). Animal experiments on mice showed that knockout of the YY1 gene at the early stage of cortical development increased the apoptosis rate of neuroepithelial cells (NECs) and neural precursor cells (NPCs) and led the cell to stay in the G1/S phase (Martins Peçanha et al, 2022), which led to neurodevelopmental defects by affecting the development of neurons. This is consistent with the case of motor retardation as the first manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…YY1 has been implicated in DNA damage recognition in β-cells 16 . To investigate whether YY1 responds to DNA damage in renal cells, HK-2 cells were treated with etoposide, a classic inducer of DNA damage 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Yin Yang 1 (YY1) is a zinc finger DNA-binding protein and a member of the GLI-Krüppel family. Accumulating evidence have suggested that YY1 could participate in numerous biological functions, such as cell proliferation [35][36][37], apoptosis [38][39][40], epithelialmesenchymal transition (EMT) [41,42] and drug resistance [43][44][45]. For triple-negative breast cancer, YY1 has also been identified as a critical promoter for tumor proliferation and invasion [25,26].…”
Section: Discussionmentioning
confidence: 99%